Estudantes bolsistas PROUNI e o curso de pedagogia da PUCRS : do acesso à permanência - Santos, Ângela Ribas dos (2016)
This research focuses on highlight the difficulties faced by Prouni scholarship students, to remain in higher education. The object of this study were students of Faculty Education at a private higher education institution in Porto Alegre. The research has the focus on quantitative and qualitative analysis, and the data is considered by content analysis. The analysis of the information obtained, showed that the main difficulty for these students is related to the lack of time to devote to studies, followed by material difficulties to stay in college. Also, the survey identified similarities between scholarship and non-scholarship students. We conclude that there is no significant difference between these two groups, we believe that the profile of these students belongs to a new audience that is entering the private higher education. This openness is linked to investment in public policies that began to create opportunities to democratize access to higher education, facilitating, thus, access to university for a public, coming from popular families.